Molecular Identification of Nocardia Isolates from Clinical Samples and an Overview of Human Nocardiosis in Brazil - Pereira Baio, Paulo Victor; Ramos, Juliana Nunes; Santos, Louisy Sanches dos; Soriano, Morgana Fonseca; Ladeira, Elisa Martins; Souza, Monica Cristina; Ferreira Camello, Thereza Cristina; Ribeiro, Márcio Garcia [UNESP]; Hirata Junior, Raphael; Vieira, Veronica Viana; Mattos-Guaraldi, Ana Luiza (Public Library Science, 2013)
BackgroundNocardia sp. causes a variety of clinical presentations. The incidence of nocardiosis varies geographically according to several factors, such as the prevalence of HIV infections, transplants, neoplastic and rheumatic diseases, as well as climate, socio-economic conditions and laboratory procedures for Nocardia detection and identification. In Brazil the paucity of clinical reports of Nocardia infections suggests that this genus may be underestimated as a cause of human diseases and/or either neglected or misidentified in laboratory specimens. Accurate identification of Nocardia species has become increasingly important for clinical and epidemiological investigations. In this study, seven clinical Nocardia isolates were identified by multilocus sequence analysis (MLSA) and their antimicrobial susceptibility was also determined. Most Nocardia isolates were associated to pulmonary disease.Methodology/Principal Findings The majority of Brazilian human isolates in cases reported in literature were identified as Nocardia sp. Molecular characterization was used for species identification of Nocardia nova, Nocardia cyriacigeorgica, Nocardia asiatica and Nocardia exalbida/gamkensis. Data indicated that molecular analysis provided a different Nocardia speciation than the initial biochemical identification for most Brazilian isolates. All Nocardia isolates showed susceptibility to trimethoprim-sulfamethoxazole, the antimicrobial of choice in the treatment nocardiosis. N. nova isolated from different clinical specimens from one patient showed identical antimicrobial susceptibility patterns and two distinct clones.Conclusions/Significance Although Brazil is the world's fifth-largest country in terms of land mass and population, pulmonary, extrapulmonary and systemic forms of nocardiosis were reported in only 6 of the 26 Brazilian states from 1970 to 2013. A least 33.8% of these 46 cases of nocardiosis proved fatal. Interestingly, coinfection by two clones may occur in patients presenting nocardiosis. Nocardia infection may be more common throughout the Brazilian territory and in other developing tropical countries than is currently recognized and MLSA should be used more extensively as an effective method for Nocardia identification.Author Summary Nocardiosis is an in common and potentially life-threatening infection. Most cases occur in immunocompromised patients, and a delay in establishing the diagnosis is due to the difficulties in clinical diagnosis and in cultivating and detecting Nocardia. Growth of Nocardia species in culture media is slow and incubation should be carried out for at least two weeks to detection this microorganism from clinical specimens. Accordingly, high levels of suspicion on the part of the clinician and of experience on the part of laboratory personnel are essential for detection of nocardiosis. In Brazil, clinical reports of Nocardia infections are scarce and the knowledge of the clinical impact of nocardiosis is fragmentary, suggesting that this genus may be underestimated as a cause of human diseases and/or neglected. In this study conventional biochemical method led to the misidentification of Brazilian isolates. Herein, molecular characterization of four loci was precisely identified as N. nova, N. cyriacigeorgica, N. asiatica and N. exalbida or N. gamkensis species. To the best of our knowledge, these are the first reported cases of human infection due to these Nocardia species in Brazil. Molecular methods offer a time-saving and accurate identification of the Nocardia genus at the species level and thus, play an important role in the diagnosis and treatment of nocardiosis.